Organic Matrix Assisted Low‐temperature Crystallization of Black Phase Inorganic Perovskites. (7th October 2021) - Chen, Yuetian; Liu, Xiaomin; Zhao, Yixin
Abstract: All‐inorganic perovskites have attracted increasing attention for applications in perovskite solar cells (PSCs) and optoelectronics, including light‐emitting devices (LEDs). Cesium lead halide perovskites with tunable I/Br ratios and a band gap aligning with the sunlight region are promising candidates for PSCs. Although impressive progress has been made to improve device efficiency from the initial 2.9 % with low phase stability to over 20 % with high stability, there are still questions regarding the perovskite crystal growth mechanism, especially at low temperatures. In this Minireview, we summarize recent developments in using an organic matrix, including the addition and use of organic ions, polymers, and solvent molecules, for the crystallization of black phase inorganic perovskites at temperatures lower than the phase transition point. We also discuss possible mechanisms for this low‐temperature crystallization and their effect on the stability of black phase perovskites. We conclude with an outlook and perspective for further fabrication of large‐scale inorganic perovskites for optoelectronic applications. Abstract : An organic matrix can assist the crystallization of all‐organic perovskites at temperatures lower than the phase transition point of black phase CsPbX3 perovskite. This low‐temperature crystallization takes place through the formation and decomposition of an intermediate state which is reminiscent of an organic–inorganic perovskite matrix.